2017
DOI: 10.1103/physrevc.96.015503
|View full text |Cite
|
Sign up to set email alerts
|

Muon-neutrino-induced charged-current pion production on nuclei

Abstract: Background: Long-baseline experiments such as T2K, NOvA or the planned Deep Underground Neutrino Experiment require theoretical descriptions of the complete event in a neutrino-nucleus reaction. Since nuclear targets are used this requires a good understanding of neutrino-nucleus interactions.Purpose: One of the dominant reaction channels in neutrino-nucleus interactions is pion production. This paper aims for a theoretically consistent treatment of all charged current charged pion production data that are ava… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 39 publications
3
23
0
2
Order By: Relevance
“…This is also found in the GiBUU prediction of Ref. [49], where it is argued that coherent pion production could provide additional strength in this region. In the comparison of the hybrid-RPWIA model with MiniBooNE and MINERvA 1π + data, pion momenta up to approximately 500 MeV were studied [30].…”
Section: B Nuwro and Final State Interactionssupporting
confidence: 73%
“…This is also found in the GiBUU prediction of Ref. [49], where it is argued that coherent pion production could provide additional strength in this region. In the comparison of the hybrid-RPWIA model with MiniBooNE and MINERvA 1π + data, pion momenta up to approximately 500 MeV were studied [30].…”
Section: B Nuwro and Final State Interactionssupporting
confidence: 73%
“…The tension between MINERvA's nuclear data and the constraints from ANL and BNL nucleon data is difficult to confidently pinpoint; the lack of lepton mass effects [51], modification to the resonance propagator in the nucleus [52,53], missing diagrams describing the non-resonant background contributions [9], dynamical coupled channels [54], interactions on correlated initial states, and the pion FSI model [1] are all part of an incomplete list of possible culprits.…”
Section: The Parameters M Resmentioning
confidence: 99%
“…There are tensions between published data from the T2K, MiniBooNE, and MINERvA experiments [1][2][3][4][5]. These tensions exist in the charged current production of both zero and one pion final states, and a model has yet to emerge that can reliably simulate all experiments at once.…”
Section: Introductionmentioning
confidence: 99%
“…This reflects the fact that the pion production cross section on nuclei shows a distinct forward peaking as can directly be read off from comparing the topmost dash-dotted-dotted curve representing the fully inclusive cross section with the solid curve representing the cross section for 0-pion events (see also Fig. 5 in [10]. At the most forward angles the stuck-pion contribution is significantly larger than the 2p2h contribution.…”
Section: A C Targetmentioning
confidence: 82%
“…More recently T2K has also obtained data on pion production, * Contact e-mail: mosel@physik.uni-giessen.de both on CH [8] and on H 2 O as targets [9] in an energy range close to that of MiniBooNE. We have analyzed the latter data in [10] 1 . There we have shown that the data sets from T2K and from MINERvA, in different energy regimes and on different targets, can be described simultaneously within the same consistent theory.…”
Section: Introductionmentioning
confidence: 99%